Bolsa-escola e inclusão educacional em Jaboticabal (SP) - Costa, Maria Christina Dória (Universidade Federal de São Carlos, 2006)
This work studies the School Stipend Program in order to verify whether or not it has achieved the goals of guaranteeing that children attend school and acquire literacy. In addition, it examines whether or not school helps the social integration of children from lowincome families. In this regard, this research project about the School Stipend Program also analyzes the extent to which this government program on a federal level can be considered a strategy for the social inclusion of poor children and adolescents. The categories of the State, Social Policies, State shape the understanding of the questions of social inclusion and exclusion in a capitalist society. The empirical study carried out between 2005 and 2006 focused on the School Stipend Program in the city of Jaboticabal, State of São Paulo. This study followed the administration of the program from its inception, collecting data that allowed the researcher to get to know the schools involved in the program and to choose the one that had the largest number of participants in the program. After contacting the selected school, the administrators and nine teachers maintained a close relationship with the students who benefited from the Program. After identifying this children, six families were selected to be visited and interviewed. Among the most important results of this study was the finding that the Program is important for the everyday life of these families, reflected in the relationship of the family and the children and adolescents with the school and in the reaffirmation of the fact that the the school remains a reference for the education of individuals. At the same time, the School Stipend Program doesn´t provide significant changes in the expansion of the social network of family support. This income supplement, regardless of the fact that it has been considered modest, has not solved the challenges that limit the possibilities in the social realm since they are the result of structural problems unemployment and low income among poor families. Finally, the school is a reference for students, an essential social instrument for the strengthening of the social support network of the most Brazilian children and adolescents who live on the fringes of vulnerability in a constantly precarious state that can produce social integration.
Keywords: Políticas públicas; Inclusão escolar; Inclusão social; Relação escola-família; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS